2015
DOI: 10.18433/j3fc7f
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of the Polymorphisms of COX-1, UGT1A6, and CYP2C9 among Cardiovascular Disease (CVD) Patients Treated with Aspirin

Abstract: PURPOSE:  Enzymes potentially responsible for the pharmacokinetic variations of aspirin include cyclooxygenase-1 (COX-1), UDP-glucuronosyltransferase (UGT1A6) and P450 (CYP) (CYP2C9). We therefore aimed to determine the types and frequencies of variants of COX-1 (A-842G), UGT1A6 (UGT1A6*2; A541G and UGT1A6*3; A522C) and CYP2C9 (CYP2C9*3; A1075C) in the three major ethnic groups in Malaysia. In addition, the role of these polymorphisms on aspirin-induced gastritis among the patients was investigated. METHODS: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For a more in-depth understanding of these DEGs, we analyzed the selected genes for GO and REACTOME pathway enrichment analyses and found that GO terms and signaling pathways were significant. [106], FCN1 [107], CARNS1 [108], AMH (anti-Mullerian hormone) [109], E2F1 [110], PF4 [111], RPL3L [112], TRIM72 [113], HOXB4 [114], TP73 [115], KCNH2 [116], (advanced glycosylation end-product specific receptor) [117], SMPD3 [118], TYMP (thymidine phosphorylase) [119], RIPPLY3 [120], GREM1 [121], CYP11B2 [122], MYLK2 [123], WNT3A [124], MSX1 [125], COMP (cartilage oligomeric matrix protein) [126], FLI1 [127], ACTA1 [128], TCAP (titincap) [129], TUBB1 [130], TNNI3 [131], HSPB7 [132], DES (desmin) [133], RAP1B [134], TNNT1 [135], BHMT (betaine--homocysteine S-methyltransferase) [136], ANGPTL3 [137], CYP3A5 [138], KMO (kynurenine 3-monooxygenase) [139], HMGCS2 [140], AGXT2 [141], FABP1 [142], SLC22A12 [143], CUBN (cubilin) [144], MIOX (myo-inositol oxygenase) [145], FBP1 [146], ARG2 [147], FGF1 [148], CRY1 [149], PPARGC1A [150], UGT1A6 [151], ECHDC3 [152], CYP2C8 [153], ACOX2…”
Section: Discussionmentioning
confidence: 99%
“…For a more in-depth understanding of these DEGs, we analyzed the selected genes for GO and REACTOME pathway enrichment analyses and found that GO terms and signaling pathways were significant. [106], FCN1 [107], CARNS1 [108], AMH (anti-Mullerian hormone) [109], E2F1 [110], PF4 [111], RPL3L [112], TRIM72 [113], HOXB4 [114], TP73 [115], KCNH2 [116], (advanced glycosylation end-product specific receptor) [117], SMPD3 [118], TYMP (thymidine phosphorylase) [119], RIPPLY3 [120], GREM1 [121], CYP11B2 [122], MYLK2 [123], WNT3A [124], MSX1 [125], COMP (cartilage oligomeric matrix protein) [126], FLI1 [127], ACTA1 [128], TCAP (titincap) [129], TUBB1 [130], TNNI3 [131], HSPB7 [132], DES (desmin) [133], RAP1B [134], TNNT1 [135], BHMT (betaine--homocysteine S-methyltransferase) [136], ANGPTL3 [137], CYP3A5 [138], KMO (kynurenine 3-monooxygenase) [139], HMGCS2 [140], AGXT2 [141], FABP1 [142], SLC22A12 [143], CUBN (cubilin) [144], MIOX (myo-inositol oxygenase) [145], FBP1 [146], ARG2 [147], FGF1 [148], CRY1 [149], PPARGC1A [150], UGT1A6 [151], ECHDC3 [152], CYP2C8 [153], ACOX2…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of enzymes like UDP-glycolaldehyde transferase, cytochrome P450, and heterologous/medium-chain fatty acid CoA ligase were thought to be the underlying mechanism of aspirin intolerance. 32,33 Cilostazol is a specific and strong inhibitor of PDE3 in platelets and smooth muscle cells, where it diminishes intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of aspirin intolerance has not been well explained yet. Polymorphisms of enzymes like UDP‐glycolaldehyde transferase, cytochrome P450, and heterologous/medium‐chain fatty acid CoA ligase were thought to be the underlying mechanism of aspirin intolerance 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…CYP2C9 metabolism primarily involves NSAIDs and aspirin, though it is also the system that metabolizes phenytoin and warfarin. A recent study noted that the genetic screening of patients for defective variants of UGT1A6 (see below) and CYP2C9 helped identify those patients at risk for gastritis from aspirin use [ 37 ]. Up to 31 defective variants of the CYP2C9 have been found to cause reduced clearance of diclofenac [ 38 ], potentially increasing the risk of GI and renal adverse events.…”
Section: Opioid Metabolismmentioning
confidence: 99%